Case Report: Detection of SARS-CoV-2 From Cerebrospinal Fluid in a 34-Month-Old Child With Encephalitis - Cheraghali, Fatemeh; Tahamtan, Alireza; Hosseini, Seyed Ahmad; Gharib, Mohammad Hadi; Moradi, Abdolvahab; Razavi Nikoo, Hadi; Tabarraei, Alijan (Frontiers in Pediatrics, 2021)
Novel coronavirus (severe acute respiratory syndrome-coronavirus-2: SARS-CoV-2), which arose from Wuhan, China, has rapidly spread to other countries and developed into a pandemic. Although the respiratory manifestations of SARS-CoV-2 are well documented, there is a considerable challenge regarding the direct and/or indirect infection in other organs. Several preliminary reports confirmed neurological manifestations in the SARS-CoV-2 infected patients. Here, we report the detection of SARS-CoV-2 from the nasopharyngeal swab and cerebrospinal fluid (CSF) in a 34-month-old child with encephalitis. This finding expands the spectrum of the neurological manifestations associated with SARS-CoV-2 infection.